Integrating Registered Dietitian Nutritionists Into Primary Care Practices to Work With Children With Overweight. Issue 2 (March 2020) - Silberberg, Mina; Carter-Edwards, Lori; Mayhew, Meghan; Murphy, Gwendolyn; Anstrom, Kevin; Collier, David; Evenson, Kelly R.; Perrin, Eliana M.; Shin, Jin-Hee; Kolasa, Kathryn M.
Despite increased reimbursement for registered dietitian nutritionists (RDNs), few studies have assessed the potential of integrating them into primary care clinics to support pediatric weight management. To assess the feasibility and effectiveness of this approach, RDNs were introduced into 8 primary care practices in North Carolina. This mixed-methods study combined (1) interviews and focus groups with RDNs and clinic personnel, (2) comparison of change in body mass index (BMI) z-score in study practices to change in historical comparison groups, and (3) analysis of behavior and BMI change for RDN utilizers. Qualitative data were coded thematically, and McNemar's and Wilcoxon signed-rank tests were used for quantitative data. RDN integration was good, but average referral rate for eligible children was 19.4%; 48.4% of those referred utilized the RDN (most fewer than 3 times). Using the full analysis set, there was no difference in change in BMI z-score for intervention and comparison groups. For RDN utilizers, the average change in BMI z-score was −0.089 (P < .001), and there was statistically significant improvement in 7 of 8 health behaviors. Integrating RDNs into primary care practices was feasible and possibly effective for utilizers. Reaping potential benefits of RDN co-location would require increasing low referral and utilization rates.